Sistem Pembiayaan KPR Sejahtera Fasilitas Liquiditas Pembiayaan Perumahan (FLPP) Dengan Akad Murabahah Bagi Masyarakat Berpenghasilan Rendah (MBR) - Nurbaeti, Siti (Expensive: Jurnal Akuntansi dan Keuangan, 2023)
The study aims to determine the suitability of the Prosperous KPR Financing System Housing Financing Liquidity Facility (FLPP) for Low-Income Communities (MBR) with a Murabahah Agreement at PT. Bank Syariah Indonesia kcp abdullah bin Nuh Abn 1 Cianjur with DSN-MUI/IV/2000 Fatwa. Data collection techniques using Participatory Observation interviews, documentary studies, triangulation, secondary data and primary data. The result of this study indicate that PT. Bank Syariah Indonesia KCP Abdullah bin nuh cianjur does not fully reflect the fatwa form the national sharia council No:04/SN-MUI IV/2000 concering murabaha.The violation occurred in term of ownership of goods (milkiyah) in the third point, namely the bank should buy goods needed by the costumer on behalf of thebank itself, but in practice the bank bus onbehalf pn the costumer and back completes the murabhah contract first to the new customer to enter ito a wakalah contract.